Consolidating gender mainstreaming in national climate policy: Lessons and recommendations for NDCs and the National Climate Change Action Plan (NAPCC) - Paez Valencia, Ana Maria; Valiente, Regina; Lizarazo, Miguel; Borrayo, Andrea; Martinez Baron, Deissy (2025)
This policy brief analyzes the integration of gender equality and social inclusion within Guatemala’s climate policy framework, with the aim of providing technical evidence to inform the updating of the Nationally Determined Contribution (NDC) and the National Climate Change Action Plan (PANCC). The analysis draws on a review of the literature, institutional interviews, and a systematic assessment of the 22 Departmental Climate Change Adaptation Plans (PDACC), conducted by means of a standardized Excel-based analysis matrix. The qualitative and comparative evaluation of adaptation measures was based on a contextualized GESI framework, grounded in the gender-responsive adaptation dimensions proposed by Dazé and Dekens (2017) and operationalized through the Reach–Benefit–Empower–Transform (RBET) framework developed by Crossland et al. (2022), enabling the classification of actions according to their level of inclusiveness.